2015
DOI: 10.1016/j.rmcr.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax due to leukemic infiltration in a patient with chronic lymphocytic leukemia

Abstract: Chylothorax is characterized by accumalation of milky fluid called chyle into the plural space. Most common causes of cyhlothorax are trauma or surgery of thoracic duct and malignancies. Among the malignancies lymphoma is responsible approximately 70% of cyhlothorax but other lymphocytic tumors including chronic lymphocytic leukemia (CLL) is rarely reported. A 71 years old man with known CLL, presented with dispnea and pleural effusion and diagnosed cyhlothorax due to leukemic infiltration that confirmed by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…The patient received no treatment, and chylothorax occurred during the observation period. As shown in this case, flow cytometric analysis of pleural fluid showed that cell surface markers including CD3, CD5, CD19, CD20 were positive, consistent with CLL, which confirmed that the chylothorax in our patient was associated with leukemic infiltration (10,13). The management of pleural effusion caused by hematological malignancies is challenging.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The patient received no treatment, and chylothorax occurred during the observation period. As shown in this case, flow cytometric analysis of pleural fluid showed that cell surface markers including CD3, CD5, CD19, CD20 were positive, consistent with CLL, which confirmed that the chylothorax in our patient was associated with leukemic infiltration (10,13). The management of pleural effusion caused by hematological malignancies is challenging.…”
Section: Discussionsupporting
confidence: 78%
“…In general, the initiation of treatment depends on the Rai and Binet staging system and the presence of disease-related symptoms or not (10). Chylothorax, as a result of CLL, has only been reported in dozens of cases and rarely occurs during the late stage of the disease (12,13). Four months before the visiting to us, our patient was found to have multiple lymphadenopathies in the whole body during a routine physical examination and diagnosed with CLL/SLL in other hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The most common cause of malignancy associated with chylothorax is lymphoma, which is present in over 70% to 75% of cases. [ 5 , 6 ] Chylothorax associated with germ cell tumors, as was the case in our patient, has previously not been reported.…”
Section: Discussionsupporting
confidence: 59%
“…Chylothorax may be caused by infections, pleural involvement and lymphatic obstruction, central catheterization and rarely by radiotherapy in patients with malignancies (3,4). Granulomatous infections such as tuberculosis and histoplasmosis have been reported as the cause of chylothorax by compressive or other effects of mediastinal lymphadenitis (5,6).…”
Section: Discussionmentioning
confidence: 99%